Evaluating Performance of Utilizing Onshore Wind Turbines Specifically the Farm Turbines in Kuwait - Alsubai'e, Mohammed Salem; Alshatti, Saad Abdullah (Engineering International, 2019)
Renewable energy is considered one of the most important and clean sources; since it does not produce any type of emission or pollution. In Kuwait, the energy of wind is existing in three main locations, which are; Ras Jal Aliyah, Bubian in addition to Subiyah, where the characteristics of wind have been evaluated in this paper based on the data generated from the meteorological measurements at 10m height. Also, different studies have been performed in this paper in order to analyze the impact of height on the parameters of wind energy, wind density, in addition to wind speed. Jal Aliyah location has been studied in this paper and the results showed that there is a proportional relation between the wind speed and power, where the maximum power is potential if the speed is equal to 29.1 m/s, and the maximum averaged flux of wind power is equal to 725.54 W/m2. Where both Bubidan Island and Ras Subiyah showed the wind direction in the North-East quadrant with speed is greater than 10 m/s. But, the higher polarized distribution of Jal Aliyah was in the north direction. Based on the obtained results, it can be concluded that this paper provides and suggests a proper design of the wind turbines for designers.